Asuhan Kebidanan Neonatus Pada Bayi Di Puskesmas Bontobangun Kecamatan Rilau Ale Kabupaten Bulukumba Tahun 2023 - Eka Juniali, Sri; Tenri Fada, Besse; Wiriyanti, Murida (Jurnal Medisains Kesehatan, 2023)
Neonates are a normal process, but this condition can turn abnormal if supervision is not carried out. Complications that can occur are one of the causes of irregular neonatal visits. So comprehensive midwifery care is needed, where this care is expected to be able to minimize complications that can occur in neonates. The aim is to provide comprehensive care for NY "A" babies. The method used is a qualitative method with a case study approach. The results of comprehensive midwifery care for babies NY "A" with normal neonates have been known from the results of observations which indicated that there were no problems since midwifery care was carried out from visits KN 1 to KN 3. the results of this study can be concluded, that from comprehensive midwifery care for babies NY "A" was carried out according to standards of care obstetrics with normal results without any complications.